Economic Waves of Power: India and China’s Strategic Pursuits in the Indian Ocean Basin - Ali, Nadia Zaheer; Bukhari, Syeda Mahnoor (Annals of Human and Social Sciences, 2024)
Indian Ocean is one of the significant geostrategic occean due to its role in the global trade and energy flows, and as a contested space for major powers like India, China and the United States. The objective of this study is to analyze the contrasting economic significance of the Indian Ocean for India and China, particularly. The Indian Ocean, being a major maritime trade route, plays a pivotal role in global commerce and energy transport forming the background for this analysis. This research adopts a qualitative approach, reviewing policy documents, existing literature and comparative studies of India and China’s strategies in the Indian Ocean Basin. The results highlight that both nations rely heavily on the Indian Ocean for securing energy imports, accessing markets, and asserting influence in global trade. The study recommends that both nations strengthen cooperative mechanisms to ensure stability and mutual economic growth while balancing competition over strategic maritime dominance.